Characterizing Cubics!

Algebra Level 5

f ( x ) = x 3 + p x + q \large{f(x) = x^3 + px + q}

Let f ( x ) = 0 f(x) = 0 be a cubic equation such that;

  • it has one repeated root of multiplicity 2, and

  • p p and q q are integers such that q = n p q=np for the least permissible positive integer n n .

Find the value of p + q p+q .


The answer is -81.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Let the repeated root be a a and the third root b . b. Then

f ( x ) = ( x a ) ( x a ) ( x b ) = x 3 ( 2 a + b ) x 2 + ( a 2 + 2 a b ) x a 2 b . f(x) = (x - a)(x - a)(x - b) = x^{3} - (2a + b)x^{2} + (a^{2} + 2ab)x - a^{2}b.

Comparing like coefficients to f ( x ) = x 3 + p x + q f(x) = x^{3} + px + q informs us that

  • 2 a + b = 0 b = 2 a , 2a + b = 0 \Longrightarrow b = -2a,

  • a 2 + 2 a b = p a 2 + 2 a ( 2 a ) = 3 a 2 = p a^{2} + 2ab = p \Longrightarrow a^{2} + 2a(-2a) = -3a^{2} = p and

  • a 2 b = q a 2 ( 2 a ) = 2 a 3 = q . -a^{2}b = q \Longrightarrow -a^{2}(-2a) = 2a^{3} = q.

Now if a = 0 a = 0 then we would have b = 0 , b = 0, so given that the repeated root has a multiplicity of precisely 2 2 we must have a 0. a \ne 0.

Now with a 2 = p 3 a^{2} = -\dfrac{p}{3} we have that q = 2 a a 2 = 2 3 a p . q = 2a*a^{2} = -\dfrac{2}{3}ap.

Thus to make q q the least possible positive integral multiple of p p we choose a = 3 , a = -3, giving us q = 2 p . q = 2p.

Then with a = 3 a = -3 we find that p = 3 a 2 = 27 p = -3a^{2} = -27 and q = 2 p = 54 , q = 2p = -54, for which p + q = 81 . p + q = \boxed{-81}.

Satyajit Mohanty Nice question. I think that for sake of clarity you might want to rephrase the first condition as "it has one repeated root of multiplicity 2 2 " to rule out the possibility of having 0 0 as a root of multiplicity 3. 3.

Brian Charlesworth - 5 years, 9 months ago

Log in to reply

Thanks for pointing that out. I've edited the problem for clarity. And, your solution is Brilliant.

Satyajit Mohanty - 5 years, 9 months ago

Log in to reply

Thank you! :)

Brian Charlesworth - 5 years, 9 months ago

@Satyajit Mohanty @Brian Charlesworth I think the statement "q is the smallest permissible positive integral multiple of p" should be improved for clarity. I thought that q is the smallest positive integral value which is a multiple of p. And consequently I got p=-27 and q=54, giving p+q=27.

BTW Nice Problem with a nice solution!

Sandeep Bhardwaj - 5 years, 9 months ago

Log in to reply

Yes, I can see how it could be interpreted that way. Would something like " p p and q q are integers such that q = n p q = np for the least permissible positive integer n n " provide clarity?

Brian Charlesworth - 5 years, 9 months ago

Log in to reply

Yeah it will!

Sandeep Bhardwaj - 5 years, 9 months ago

Thanks. I've amended the problem :)

Satyajit Mohanty - 5 years, 8 months ago

the second statement didnt seem to say n to be an integer, but a positive

Aareyan Manzoor - 5 years, 8 months ago

Log in to reply

You're right, it really should read as "positive integer n n ". A previous phrasing of the question made it clear that n n must be integral, while now it is implicit, (since the letter n n is usually reserved for integers). Perhaps Satyajit may choose to add the word "integer" to make that condition more explicit.

Brian Charlesworth - 5 years, 8 months ago

Log in to reply

i assumed n not to be integral and gave answer 0,sir.should i be marked?

Aareyan Manzoor - 5 years, 8 months ago

Log in to reply

@Aareyan Manzoor Referring to my solution, in order to have p + q = 0 p + q = 0 we would require that

3 a 2 + 2 a 3 = 0 a 2 ( 2 a 3 ) = 0 , -3a^{2} + 2a^{3} = 0 \Longrightarrow a^{2}(2a - 3) = 0, in which case either a = 0 a = 0 or a = 3 2 . a = \dfrac{3}{2}.

If a = 0 a = 0 then since 2 a + b = 0 2a + b = 0 we would require that b = 0. b = 0. But since by the first condition not all three roots can be the same, we cannot have a = 0. a = 0.

If a = 3 2 a = \dfrac{3}{2} then p = 3 a 2 = 27 4 p = -3a^{2} = -\dfrac{27}{4} and q = 2 a 3 = 27 4 , q = 2a^{3} = \dfrac{27}{4}, which would give us q = p q = -p and thus n = 1 , n = -1, which is not positive.

So an answer of 0 0 would not be consistent with the condition that n n be positive, regardless of whether or not it is an integer. So unless I'm mistaken, I don't think an answer of 0 0 can be considered as correct. Sorry. :( Did you try any values other than 0 0 on your three attempts?

Brian Charlesworth - 5 years, 8 months ago

Discriminat must be zero because of a root has multiplicity of 2. 4 p 3 27 q 2 = 0. B u t q = n p , 4 p 3 = 27 n 2 p 2 , b u t p 0. p < 0 , a n d n 2 = 4 p 27 . B u t p a n d n a r e i n t e g e r s , n > 0. m i n i m u m v a l u e o f n w o u l d b e w h e n p = 27 , n = 2. q = 2 ( 27 ) = 54. p + q = 81 \therefore~ - 4*p^3 - 27q^2=0.~~But~q=n*p,~~\implies~- 4*p^3=27*n^2*p^2,~ but~p\neq0.\\ \therefore~p<0,~and~n^2= - \dfrac{4*p}{27}.~~~But~p~and~n~are~integers, ~n>0.\\ \therefore~minimum~value~ of~ n~ would~ be~ when~ p= - 27, n=2.~~ \implies q= 2*( - 27)= - 54.\\ p+q= \Large~~~\color{#D61F06}{ - 81}\\~~\\

Just an addition. Since cof. of x square is zero, and a root with multiplicity 2, we can say that the roots are r, r, -2r, and ( 54 ) = 2 r 3 . -( - 54)=2*r^3.~~\therefore the roots are -3, -3, 6. Note that q is twice the cube of a number.
I use TI-83 calculator. For graphing window[ -4,7] in X, with [-1,1] I got graph touching x-axis. But Y-window [ - 0.1, 0.1], it showed the graph is not touching. If it is an intersection, 1 E -10 gives very good result, but be careful when it is touching graph. In fact this problem also was first solved in TI-83 by graphing:- X 3 + p ( X + n ) , X^3+p*( X+n), and setting p+1-->p. With - 30<X<30 . We can see with increase in n, the curve moving down. Only 1<= n<=3 was needed.

Ruslan Abdulgani
Sep 18, 2015

f(x) = (x – a)^2(x+(np)/a2) = x^3 + [(np/a^2) – 2a]x^2 + (a^2 – 2np/a) x +np. From (np/a^2) – 2a = 0, we get p=2a^3/n, and from a^2 – 2np/a = p, - 3a^2 = 2a^3/n, n=2a/-3, smallest n=2, for a=-3.So p=-27. f(x)=(x+3)2(x – 6) = x3 – 27x – 54 =0, p+q= -27 – 54 = -81

f ( x ) = ( x a ) 2 ( x + ( n p ) / a 2 ) = x 3 + [ ( n p / a 2 ) 2 a ] x 2 + ( a 2 2 n p / a ) x + n p . F r o m ( n p / a 2 ) 2 a = 0 , w e g e t p = 2 a 3 / n , a n d f r o m a 2 2 n p / a = p , 3 a 2 = 2 a 3 / n , n = 2 a / 3 , s m a l l e s t n = 2 , f o r a = 3. S o p = 27. f ( x ) = ( x + 3 ) 2 ( x 6 ) = x 3 27 x 54 = 0 , p + q = 27 54 = 81 In order to understand your work, I have copied your work as above. f(x) =~~ (x - a)^2(x+(np)/a2)\\ =~~ x^3 + [(np/a^2) - 2a]x^2 + (a^2 - 2np/a) x +np.\\ From~ (np/a^2) - 2a = 0,~ we ~get~~~ p=2a^3/n,~ and~ from ~~~a^2 - 2np/a = p,\\ - 3a^2 = 2a^3/n,~~~~ n=2a/-3,~ smallest~ n=2,~ for~ a=-3.~~So ~~p=-27.\\ f(x)=(x+3)2(x - 6) = x3 - 27x - 54 =0,~~ p+q= -27 - 54 = -81\\ \text{In order to understand your work, I have copied your work as above.}

Niranjan Khanderia - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...